Aggressive Angiomyxoma in the Scrotum: A Case Series and Literature Review - Sun, Juan; Lian, Peng H.; Ye, Zi X.; Dong, De X.; Ji, Zhi G.; Wen, Jin; Li, Han Z. (Frontiers in Surgery, 2022)
Purpose: Aggressive angiomyxoma (AAM) was identified as a distinct clinicopathological entity in 1983. Since then, a few cases of its occurrence in the scrotum have been reported. This case series was performed to increase clinicians’ understanding of the clinical features and treatment of AAM in the scrotum. Methods: We evaluated the clinical presentations, treatments, and follow-up of two patients with AAM in the scrotum in our hospital and 34 cases reported in the literature. Results: Among the 36 patients, the average age was 48.3±20.6 years old (range from 1 to 81); the average maximum diameter of the tumor was 8.36 cm (1.6-25 cm); the site of one (2.78%) patient was located in the epididymis, 2 (5.56%) in the testes, 5 (13.89%) in the spermatic cord, and 28 (77.77%) in the scrotum. The clinical symptoms were generally non-specific and 20 patients inadvertently discovered their slow-growing painless masses. The treatments for all these patients were surgical excision once the tumor had been found and one case underwent excision followed by radiotherapy. The median follow-up time for the remaining 32 cases was 24.5 months (1 to 84 months). Recurrence occurred in 3 cases (9.09%) at the primary sites and no cases of distant metastasis. Conclusion: AAM of the scrotum can occur in middle-aged and elderly men. The clinical manifestation generally involves a long history of asymptomatic masses or swelling in the scrotum. Ultrasound is the most commonly used diagnostic technique but magnetic resonance imaging may be more effective. The mainly treatment is surgical excision and postoperative histopathological examination is still the gold standard for its diagnosis. Although it is locally aggressive, metastasis is extremely rare in males.